2 - Le plan d'action de Lagos et la Banque Mondiale. Étude comparative des deux points de vue sur l'alimentation et l'agriculture en Afrique - Mkandawire, Thandika (Africa Development, 1983)
In this article, the author compares the World Bank «Berg Report»: Accelerated Development for Africa: An Agenda for Action ana the Lagos Plan of Action. Contrary to the claims of the «Ber'g'Repôrt», the author argues that the two documents advance totally different visions of econo mic development in Africa. While the LP A seeks to achieve greater regional co-operation through a regionally inward-looking strategy, the Berg Report advances an extroverted, primary raw materials export-oriented develop ment strategy heavily dependent upon foreign capital. Given the economic crisis facing African economies, the Π odd Bank is in a better position to force through its development strategy. However the economic crisis facing countries that the Report puts forward as models — Malawi, Ivory Coast, Kenya — suggests that the option sugges the LP A is still on the agenda in Africa